Pengaruh Strategi Harga Terhadap Keputusan Pembelian Konsumen Industri Ritel Di Era New Normal - Rury Dwi Rahmayani; Desak Made Dharmawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The era of the Covid-19 pandemic until the new normal is confirmed to have affected all aspects of life, including the scope of marketing, especially the retail industry. It seems that knowing consumer decisions in making purchases is important, one of which is the influence of price strategy. Thus, this study aims to determine the effect of price strategy on purchasing decisions. Prima Freshmart was chosen as the representative object. The research method uses quantitative associative, simple linear regression data analysis technique is used with the stages of validity - reliability testing, classical assumption test, and simple linearity test, as well as non-probability sampling technique (purposive sampling) is used (obtained a sample of 88, Prima Freshmart consumers). The data processing application used is SPSS 26.0. The results of the study are that H0 is rejected and H1 is accepted, meaning that there is a significant and positive influence on the price strategy on purchasing decisions. Future research suggestions are also discussed.